2019
DOI: 10.1096/fj.201900752r
|View full text |Cite
|
Sign up to set email alerts
|

RIP3 deficiency alleviates liver fibrosis by inhibiting ROCK1–TLR4–NF‐κB pathway in macrophages

Abstract: Liver fibrosis is an important pathologic process in injured liver tissues. A protein kinase, receptor‐interacting protein (RIP)3, plays a crucial role in mediating different diseases. However, the role of RIP3 in macrophages in liver fibrosis has not yet been studied. In our study, we found that RIP3 expression was up‐regulated in liver tissues and macrophages of humans and mice with liver fibrosis. Absence of RIP3 in macrophages could alleviate inflammation and macrophage or neutrophil accumulation in mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…RIP3-dependent necrosis is widely believed to contribute to several detrimental pathologies. Conversely, RIP3 is profoundly important for inflammation, in part through regulating NF-κB activity 47 . Here, we found that TSZ-induced expression of CCR5 was severely inhibited in RIP3−/− BMDMs, and the NF-κB inhibitor PDTC blocked TSZ-induced CCR5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…RIP3-dependent necrosis is widely believed to contribute to several detrimental pathologies. Conversely, RIP3 is profoundly important for inflammation, in part through regulating NF-κB activity 47 . Here, we found that TSZ-induced expression of CCR5 was severely inhibited in RIP3−/− BMDMs, and the NF-κB inhibitor PDTC blocked TSZ-induced CCR5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Sprague‐Dawley rats (Forty) were obtained from the Anhui Medical University, Experimental Animal Center. SD rats were intraperitoneally injected twice‐weekly for 12 weeks with a mixture of carbon tetrachloride (CCl 4 )/olive oil in a 1:1 (vol/vol) ratio at 1 mL/kg . All animal experiments were approved by the Institutional Animal Care and Use Committee of Anhui Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…SD rats were intraperitoneally injected twice-weekly for 12 weeks with a mixture of carbon tetrachloride (CCl 4 )/olive oil in a 1:1 (vol/vol) ratio at 1 mL/kg. 16 All animal experiments were approved by the Institutional Animal Care and Use Committee of Anhui Medical University. Twelve weeks later, the animals were anaesthetized, the rats were then sacrificed and liver tissues collected.…”
Section: Animal Models Of Liver Fibrosismentioning
confidence: 99%
“…It was previously reported that the RhoA/ROCK pathway governed TLR4/NF-kB signaling and accelerated inflammation [32]. Previous studies have shown that ROCK1 was the upstream mediator of TLR4 in macrophages during liver fibrosis [33]. With the use of the ROCK inhibitor, Y-27632, Hutchinson et al showed that the inflammatory cascade activated TLR4 signaling through ROCK [34].…”
Section: Control Hfdmentioning
confidence: 99%